﻿Formosania immaculata, a new species of hillstream loach (Teleostei, Cypriniformes, Gastromyzontidae) from the Ou-Jiang River, Southeast China - Wei Sun; Jia-Jun Zhou; Jin-Quan Yang (ZooKeys, 2023)
Formosania immaculata, a new species, is described from the Ou-Jiang basin in Zhejiang Province, Southeast China. It is distinguished from other species of the genus by having a combination of the following characteristics: body without obvious mottling; snout length longer than postorbital length; abdominal scaleless area extending to middle of pectoral-fin base; shorter rostral barbels, the outermost pair length 112.9%–140.0% of eye diameter; and shorter lower lip papillae, length 19.9%–24.4% of eye diameter. Its validity is also affirmed by its distinct Cytb gene sequence divergence from all congeners and its monophyly recovered in a Cytb gene-based phylogenetic analysis.